SUATU TINJAUAN ISLAM: PRAKTIK “BOROH” (PEGADAIAN) (MENGATASI MASALAH DENGAN MASALAH) - Andi Irfan (Universitas Jember, 2012)
The purpose of this research is to find the interpretation of Ar-rahn or “boroh” and its implication of the perspective of marhun and rahin. Informants are from marhun and rahin in Kecamatan Pujud Kabupaten Rokan Hilir. Data is collected through interviews with informants and analysed by employing phenomenology. The results of this research show that informants often practise Ar-rahn and don't care about the sharia principles are violated. His findings murtahin utilized by marhun with permission or without the permission of rahin and ignore the maintenance costs. When the Murtahin was sold to pay off debts but the fact murtahin directly into the right marhun without any auction process. Keyword: Ar-Rahn, “Boroh”